Cordially - The untouchable. An approach on 'Le toucher, Jean-Luc Nancy' - Caneda Lowry, Santiago (Escritura e Imagen, 2019)
The untouchable, a chance of touching the untouchable and the respect of this law of touchitself, these are some of the key themes of Jacques Derrida’s Le toucher, Jean-Luc Nancy. This paperpresents a critical reading of this issues with the aim of easing and clearing the path to Derrida’s patientand rigorous work on Jean-Luc Nancy. This law of touch goes beyond the discussion on perceptionand gets on the track of an ethics involved in the very definition of this sense. A touch that no longerrefers exclusively on the sense, but on the cordiality and respect of the contact with the other. On thisroad to the core of what Nancy claims to be the untouchable, we’ll also review the caress in the work ofLévinas, as it’s one of the best examples of the risks involved when trying to touch beyond touch itself.Once this path is cleared, we’ll approach the works of Nancy on the body and its deconstruction, as alsothe great deal that he sees in a posthumous note of Freud. Finally, this paper looks for a clearer but solidaccess to the oeuvre of Jean-Luc Nancy, and its cleverness in face of the preceding phenomenologicalhighlights.
Keywords: Jacques Derrida; Jean-Luc Nancy; deconstruction; touch